Metabolic Regulation of Group 3 Innate Lymphoid Cells and Their Role in Inflammatory Bowel Disease - Song, Dongjuan; Lai, Lijie; Ran, Zhihua (Frontiers in Immunology, 2020)
Inflammatory bowel disease (IBD) is characterized by chronic and relapsing inflammatory disorder of the intestine. IBD is associated with complex pathogenesis, and considerable data suggest that innate lymphoid cells contribute to the development and progression of the condition. Group 3 innate lymphoid cells (ILC3s) not only play a protective role in maintaining intestinal homeostasis and gut barrier function, but also a pathogenic role in intestinal inflammation. ILC3s can sense environmental and host-derived signals and combine these cues to modulate cell expansion, migration and function, and transmit information to the broader immune system. Herein, we review current knowledge of how ILC3s can be regulated by dietary nutrients, microbiota and their metabolites, as well as other metabolites. In addition, we describe the phenotypic and functional alterations of ILC3s in IBD and discuss the therapeutic potential of ILC3s in the treatment of IBD.